FAKTOR-FAKTOR YANG MEMPENGARUHI RASIONALITAS PERILAKU KONSUMSI MAHASISWA FAKULTAS EKONOMI UNIVERSITAS NEGERI PADANG - Juliani Juliani; Efni Cerya (Universitas Negeri Padang, 2018)
Abstract: This research was conducted to reveal the influence of student income, parents' socio-economic status, tastes, and financial literacy on the rationality of consumption behavior of students of the Faculty of Economics, Padang State University. The type of research used is quantitative research with causal research design and descriptive method. The population in this study were the 2015, 2016, and 2017 UNP Economics Faculty undergraduate students with a sample size of 169 from a population of 1691 students. The technique used in sampling was proportionate stratified random sampling, research data was obtained through questionnaires. The research data were analyzed by multiple regression tests with the help of the SPSS version 21 application program. Keyword: Income, Socio-Economics Status, Tastes, Financial Literacy Rationality of Consumption Behavior